Interfaces and defects in a successfully hot-rolled steel-based composite Fe–TiB2. (1st October 2015) - Lartigue-Korinek, Sylvie; Walls, Michael; Haneche, Nadia; Cha, Limei; Mazerolles, Léo; Bonnet, Frédéric
Graphical abstract: Abstract: Steel-based composites reinforced with titanium diborides (TiB2 ) and produced by eutectic solidification display a significant increase in specific stiffness ( E / ρ ) in comparison with usual steels. A significant lightening can be achieved in parts designed for stiffness with a high Young's modulus and a low density. They can be produced through the use of industrial continuous casting devices and can be hot rolled without any damage. This production route guarantees a good cohesion of the steel/reinforcement interface and the control of the main parameters that determine the final properties of the product (size, shape, clustering of reinforcements). In order to get a better understanding of the composite properties, its microstructural features after hot rolling are investigated through transmission electron microscopy at microscopic and atomic levels. TiB2 reinforcements are homogeneously distributed in the ferritic iron matrix. Interfaces between Fe and TiB2 particles are mainly parallel to dense planes of the diboride, with a preferential growth of prismatic planes { 1 0 1 ¯ 0 } . Interfacial misfit dislocations occur at interfaces parallel to the prismatic planes. The TiB2 basal plane is covered by a TiC layer three atomic planes in width. The hot rolling operation induces a significant plastic deformation in the TiB2 particles, with the activation of basal and prism plane slip systems. All these characteristics may account for the good behaviour of the composite in terms of hot rolling capability.